The language of the SAAL program. Similarities and variations in the work of the SAAL Teams in Porto - Fernandes, Eduardo Jorge Cabral dos Santos (2016)
In the SAAL Program, Portuguese architects faced a paradoxical situation, given the urgency and scale of the needs of local populations and the will to apply two basic principles: the right to the city and the right to architecture. Porto architects understood the need for a pragmatic approach, to enable an effective response in the short term. The need for rationality and economy justified a language with modernist roots; so, most of the resulting housing schemes showed an uniform approach (resulting from the need to respond to similar circumstances), with common characteristics: organization in parallel volumes, often unrelated to the alignments of the pre-existing city, with long and narrow duplex dwellings, a set of stairs in the centre and openings on both the opposing façades. Although they all share similarities, we can distinguish two different approaches in the low density housing projects built in Porto: in S. Victor, Francos, Lapa and Maceda we can find a purist language and a rigid volumetry; on the contrary, Contumil, Antas, Leal and Chaves de Oliveira share an hybrid language, in which the typological and formal solutions are best suited to their specific urban environment and seem to be more agreeable to the populations.